Destructive sublime : World War II in American film and media - Allison, Tanine, 1979- (Rutgers University Press, 2018)
"The American popular imagination has long portrayed World War II as the 'good war, ' fought by the "greatest generation" for the sake of freedom and democracy. Yet, combat films and other war media complicate this conventional view by indulging in explosive displays of spectacular violence. Combat sequences, Tanine Allison argues, construct a counter-narrative of World War II by reminding viewers of the war's harsh brutality. Destructive Sublime traces a new aesthetic history of the World War II combat genre by looking back at it through the lens of contemporary video games like Call of Duty. Allison locates some of video games' glorification of violence, disruptive audiovisual style, and bodily sensation in even the most canonical and seemingly conservative films of the genre. In a series of case studies spanning more than seventy years--from wartime documentaries like The Battle of San Pietro to fictional reenactments like The Longest Day and Saving Private Ryan to combat video games like Medal of Honor--this book reveals how the genre's aesthetic forms reflect (and influence) how American culture conceives of war, nation, and representation itself"-- Provided by publisher
Keywords: World War, 1939-1945 -- Motion pictures and the war.; World War, 1939-1945 -- Mass media and the war.; War films -- United States -- History and criticism.; War video games.; Guerre mondiale, 1939-1945 -- Cinéma et guerre.; Films de guerre -- États-Unis -- Histoire et critique.; Jeux vidéo de guerre.; PERFORMING ARTS -- Reference.; PERFORMING ARTS -- Film & Video -- History & Criticism.; War video games; Mass media and war; War and motion pictures; War films; United States; 1939-1945; American.; Call of Duty.; Medal of Honor.; Saving Private Ryan.; The Battle of San Pietro.; The Longest Day.; WWII.; World War II.; combat.; destructive.; film.; media.; sublime.; video games.; war film.; war.; Criticism, interpretation, etc.